Altered brain gyrification in deficit and non-deficit schizophrenia - Takayanagi, Yoichiro; Sasabayashi, Daiki; Takahashi, Tsutomu; Komori, Yuko; Furuichi, Atsushi; Kido, Mikio; Nishikawa, Yumiko; Nakamura, Mihoko; Noguchi, Kyo; Suzuki, Michio (Psychological medicine, 2019)
Patients with the deficit form of schizophrenia (D-SZ) are characterized by severe primary negative symptoms and differ from patients with the non-deficit form of schizophrenia (ND-SZ) in several aspects. No study has measured brain gyrification, which is a potential marker of neurodevelopment, in D-SZ and ND-SZ. We obtained magnetic resonance scans from 135 schizophrenia patients and 50 healthy controls. The proxy scale for deficit syndrome (PDS) was used for the classification of D-SZ and ND-SZ. The local gyrification index (LGI) of the entire cortex was measured using FreeSurfer. Thirty-seven D-SZ and 36 ND-SZ patients were included in the LGI analyses. We compared LGI across the groups. SZ patients exhibited hyper-gyral patterns in the bilateral dorsal medial prefrontal and ventromedial prefrontal cortices, bilateral anterior cingulate gyri and right lateral parietal/occipital cortices as compared with HCs. Although patients with D-SZ or ND-SZ had higher LGI in similar regions compared with HC, the hyper-gyral patterns were broader in ND-SZ. ND-SZ patients exhibited a significantly higher LGI in the left inferior parietal lobule relative to D-SZ patients. Duration of illness inversely associated with LGI in broad regions only among ND-SZ patients. The common hyper-gyral patterns among D-SZ and ND-SZ suggest that D-SZ and ND-SZ may share neurodevelopmental abnormalities. The different degrees of cortical gyrification seen in the left parietal regions, and the distinct correlation between illness chronicity and LGI observed in the prefrontal and insular cortices may be related to the differences in the clinical manifestations among D-SZ and ND-SZ.